Treatment of hallux rigidus: allograft interpositional arthroplasty vs arthrodesis - Bennett Krumm, Drew; Jonathan Patton, Daniel; Scott Madden, Tyler; Gregory Anderson, John; Maskill, John David; Raymond Bohay, Donald; Arisleida Padley, Michelle; Behrend, Lindsey Adele (Journal of the Foot & Ankle, 2022)
Objective: Surgery for severe hallux rigidus includes interpositional arthroplasty and arthrodesis. Interpositional arthroplasty maintains joint mobility, while arthrodesis limits motion. The aim of this study was to compare changes in Visual Analog Scale and American Orthopedic Foot and Ankle Society scores between interpositional arthroplasty and arthrodesis patients. Methods: A retrospective cohort study of 48 patients was performed. There were 24 patients in the interpositional arthroplasty group and 24 patients in the arthrodesis group. A follow-up phone survey was administered from which updated Visual Analog Scale and American Orthopedic Foot and Ankle Society scores were obtained. Results: Visual Analog Scale scores improved by 4.08 (SD, 2.02) points after interpositional arthroplasty and 4.54 (SD, 3.64) points after arthrodesis. American Orthopedic Foot and Ankle Society scores improved by 28 (SD, 16) points after interpositional arthroplasty and 29 (SD, 26) points after arthrodesis. Conclusion: In hallux rigidus patients, pain improvement results were similar for both interpositional arthroplasty and arthrodesis. Interpositional arthroplasty has been reported in the literature as maintaining mobility, which is an important goal of many patients. Level of Evidence III; Therapeutic Studies; Case-Control Study.